Gut microbiota dysontogeniya in infants as a factor in the development of atopy - Irina A. Belyaeva (Pediatričeskaâ Farmakologiâ, 2019)
The article describes the modern views on the relationship between altered development of gut microbiota in infants and the risk of developing atopic diseases (atopic dermatitis and bronchial asthma). The studies of genetic susceptibility to atopy and the influence of epigenetic mechanisms involved in the regulation of gene expression responsible for the hyperproduction of immunoglobulin E are discussed. The characteristics of the microbiota of infants with already developed atopic diseases and children at risk of atopy are analyzed. In infants who subsequently developed atopy, the composition of gut microbiota at the birth is characterized by a reduced abundance of bifidobacteria  and high content of potentially pathogenic microorganisms.  The triggering role of active metabolites of altered microbiota on the differentiation of T-regulatory  cells has been established.  A preventive effect of optimal breastfeeding has been confirmed: meta-analyzes of recent studies indicate a link between the duration of breastfeeding  and a decrease in the frequency of bronchial asthma. The microbiota of breast milk contributes to the proper development of the infant’s microbiota, determines its diversity and immunomodulating action. On the basis of the conducted research, methods of targeted correction of the intestinal microbiota in children with risk of atopy can be developed.